PENGARUH JENIS AIR RENDAMAN TERHADAP PENURUNAN KADAR FORMALIN PADA IKAN TONGKOL (Euthynnus affinis) - Devi Arifatin Giyanti; Narwati .; Margono . (GEMA LINGKUNGAN KESEHATAN, 2014)
Fish is an example of perishable food. To prevent fish from deteriorating quickly, proper handlingis required during storage to extend the shelf life, among other things, one of which is by the addition ofpreservatives. the extension of food shelf lives, people often misused formaldehyde as a foodpreservative. Formaldehyde itself is banned for use as food ingredients as it may be harmful to humanhealth, such as irritation of the stomach, its carcinogenic properties (causing cancer), and may bringabout death.This was an experimental study using one group pretest-posttest design to investigate the effectof soaking water on the reduction of formaldehyde levels in cobs. There were 48 samples in 6replications of each treatment group. The dependent variable in this study was the formaldehyde levelsin cobs and the independent variables was the type of soaking water (tap water, hot water attemperature of 50 DCand 5% vinegar), soaking were exercised for 30 minutes. The data were analyzedusing paired t test and Anova test.The result showed that all three types of soaking water were able to reduce levels of formaldehydein cobs, where tap water reduced formaldehyde level by 53.7% at p a (0.05), hot water attemperature of 50 DCreduced formaldehyde level by 62.6% at p a (0.05), and vinegar 5% reducedformaldehyde level by 42.4% at p a (0.05). The Anova test between treatment groups indicated thatsoaking water resulted in a value of p a (0.05)It can be concluded that types of soaking water have no effect on the reduction of formaldehydelevel in cobs. However, there were significant differences in reduction of formaldehyde level before andafter the soaking treatment. The stydy suggested that further research needs to be conducted on otherfish samples using different concentration of soaking water and soaking time.